Administrative ethics : A conceptual framework - Rajan, Amitabh (London : Routledge, 2024)
"This insightful book explores the use and application of ethics in contemporary governance and suggests necessary reforms. Following an interdisciplinary approach involving the fields of political science, law, economics, sociology, management, and philosophy, this book analyses their applicability and usefulness in everyday practices in governance, covering its five cardinal virtues-prudence, transparency, discourse, justice, and accountability. Highlighting ethical challenges in aspects of status recognition, oppression, empowerment, social care, public financing, environment protection and others in today's interconnected world, it delves into the dynamics of administrative power in democracies and showcases how the misuse of power can be controlled through a discourse of ethics in law and governance. The book will be useful to the students, researchers and teachers of public administration, philosophy, political Science, corporate ethics, and governance other related social sciences disciplines. The book will also be an indispensable companion to social activists, advocacy groups, journalists and civil society institutions and public service training institutions"
Keywords: Political Science; Public administration/ ethics